Aspects to consider for optimizing a substrate culture system with drainage recycling (2012)
In Colombia, the soilless system has been implemented in the cut flowers industry, among others, due to soil limitations. The use of substrates as growing media implies to drain around 30% of the applied fertigation solution to avoid the rhizosphere salinization. The drainage solution is spilled out to the soil producing environmental hazards and it might reach the water table; although the drainage solution could be recycled or reuse, depending upon their chemical characteristics. The nutrient uptake by the plants depends upon their phenological stage and the nutrient concentration in the solution; which could lead to ion depletion or accumulation. In general, monovalent ions are withdrawn faster than divalent ones. An efficient drainage treatment involves the automation of sensing and evaluation of ion concentration and recycling the drainage solution. The system should take into account the chemical aspects in the recycled and the new solutions in order to predict the life time of the drainage solution from their EC and pH. The system must be integrated with disinfection methods to avoid the spreading of plant pathogens. This review point out the physiological and technical bases that should be taking into account in a drainage recycling system in established crops under substrates, as a tool to take decisions more efficiently.